Digital fluxgate magnetometer: design notes. (23rd October 2015) - Belyayev, Serhiy; Ivchenko, Nickolay
Abstract: We presented an approach to understanding the performance of a fully digital fluxgate magnetometer. All elements of the design are important for the performance of the instrument, and the presence of the digital feed-back loop introduces certain peculiarities affecting the noise and dynamic performance of the instrument. Ultimately, the quantisation noise of the digital to analogue converter is found to dominate the noise of the current design, although noise shaping alleviates its effect to some extent. An example of magnetometer measurements on board a sounding rocket is presented, and ways to further improve the performance of the instrument are discussed.